The Relation of Emergency Duties to Cardiac Death Among US Firefighters - Smith, Denise Louise; Haller, Jeannie M.; Korre, Maria; Sampani, Konstantina; Porto, Luiz Guilherme Grossi; Fehling, Patricia C.; Christophi, Costas A.; Kales, Stefanos N. (My University, 2019)
Sudden cardiac death accounted for 42% of all firefighter duty-related fatalities over the last decade. This retrospective study analyzed available medical examiner records for duty-related firefighter fatalities among male firefighters 18 to 65 years of age that occurred between 1999 and 2014 and reported the pathoanatomic substrate for cardiac-related fatalities. Odds of duty-related cardiac death during specific duties compared with fire station duties were calculated by pathoanatomic substrate. There were 285 cardiac fatalities. Of fatalities, 80% had evidence at autopsy of coronary heart disease (CHD) and increased heart size (cardiomegaly and/or left ventricular hypertrophy). CHD alone, cardiomegaly or left ventricular hypertrophy, and causes other than CHD or increased heart size were identified in 7.7%, 6.0%, and 6.7% of fatalities, respectively. The largest proportion of deaths occurred during fire suppression (33%), although only 1% of annual occupational time was estimated to be spent performing this duty. For deaths attributed to CHD and increased heart size, fire suppression, alarm response, and physical training were associated with approximately a 112-fold, eightfold, and sevenfold increased risk of cardiac death, respectively, compared with station duties. In conclusion, the majority of firefighters who suffered a duty-related cardiac death had CHD and increased heart size, which was associated with a markedly increased risk of death during fire suppression compared with station duties. Targeted occupational medical screening for CHD and increased heart size may reduce duty-related cardiac deaths among firefighters.
Keywords: Cardiomegaly; Fire fighter; Heart death; Ischemic heart disease; Heart left ventricle hypertrophy